Vibration analysis of hybrid-reinforced unsaturated polyester composites - M. Hamdan, M. H.; Siregar, J. P.; Sapuan, S. M.; Tezara, C.; M. Hafizi, Z.; M. Rejab, M. R.; Bachtiar, D.; Jamiluddin, J. (Elsevier, 2019)
Fiber-reinforced polymer composites (FRPCs) have been used extensively in the past few decades. Even today, composite materials are still rapidly improving by research around the globe. Several factors that have motivated researchers to develop FRPCs are to reduce costs, tackle environmental issues, sustain composite resources, produce a databank in regard to material design, maximize potential at elevated temperatures and high humidity, and to replace the use of metallic components. The application of FRPCs is primarily expanded in the automotive, aeronautics, structural, and manufacturing industries [1]. In order to make all the inspiration, natural fibers have become the focus of research. Many advantages may be related to the utilization of natural fiber in FRPCs. Typically, natural fiber is light, highly available, recyclable, cheap, and has acceptable mechanical and physical properties and low energy requirements [2]. Therefore natural fiber is essential as a replacement or alternative to synthetic fiber as a reinforcement material in both thermoplastic and thermoset matrix polymer composites. Nevertheless, the potential of natural fiber as a reinforcement material is often limited by its low thermal degradation, vulnerability to moisture attack, low modulus, and poor impact properties [35].